Synthesis and Characterization of Tin (IV) Tungstate Nanoparticles – A Solid Acid Catalyst - Manoj Sadanandan; Beena Raveendran (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2012)
Tin (IV) tungstate, a tetravalent metal acid salt was synthesized in the nanoform by chemical coprecipitation method using EDTA as capping agent. The material was found to be stable in mineral acids, bases and organic solvents except in HF and aquaregia. The material was characterized using EDS, TG/DTA, FTIR, XRD, SEM, HRTEM and BET surface area measurement. The molecular formula of the compound is 2SnO2 3WO3.5H2O determined from elemental analysis using TG/DTA. Surface morphology and particle size were obtained using SEM and HRTEM. The surface area was found to be 205-225m2/g. The Na+ exchange capacity found to be 3.8 meq/g, indicates the presence of surface hydroxyl group and hence the presence of Bronsted acid sites. The catalytic activity of the material was tested by using esterification and oxidation as model reactions. For the esterification of different alcohols, the percentage yield was found to be high for n-alcohol compared to isomeric alcohols. Oxidation of benzyl alcohol gives benzaldehyde and benzoic acid as the only products. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)